The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12891-019-2832-5
|View full text |Cite
|
Sign up to set email alerts
|

Are changes in radiological leg alignment and femoral parameters after total hip replacement responsible for joint loading during gait?

Abstract: BackgroundGait kinematics after total hip replacement only partly explain the differences in the joint moments in the frontal plane between hip osteoarthritis patients after hip replacement and healthy controls. The goal of this study was to determine if total hip replacement surgery affects radiological leg alignment (Hip-Knee-Shaft-Angle, femoral offset, Neck-Shaft-Angle and varus/valgus alignment) and which of these parameters can explain the joint moments, additionally to the gait kinematics.Methods22 unil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Higher CF on the contralateral (non-operated) side in the second half of stance compared to the ipsilateral side confirm the results of other studies (Shakoor et al, 2003;Foucher and Wimmer, 2012;Wesseling et al, 2018), although not all studies reported significant differences between patients (ipsilateral or contralateral) and healthy controls (Wesseling et al, 2018) so that a surplus load cannot be confirmed. The present results do support studies reporting a higher risk for the development of OA in the contralateral knee joint after THR (Shakoor et al, 2002;Umeda et al, 2009;Gillam et al, 2013;Jungmann et al, 2015;Joseph et al, 2016) since patients are walking with an asymmetrical limb load. However, these studies only report more structural damage and progression of degenerative findings in the contralateral knee and do not specify the medial or lateral knee compartment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Higher CF on the contralateral (non-operated) side in the second half of stance compared to the ipsilateral side confirm the results of other studies (Shakoor et al, 2003;Foucher and Wimmer, 2012;Wesseling et al, 2018), although not all studies reported significant differences between patients (ipsilateral or contralateral) and healthy controls (Wesseling et al, 2018) so that a surplus load cannot be confirmed. The present results do support studies reporting a higher risk for the development of OA in the contralateral knee joint after THR (Shakoor et al, 2002;Umeda et al, 2009;Gillam et al, 2013;Jungmann et al, 2015;Joseph et al, 2016) since patients are walking with an asymmetrical limb load. However, these studies only report more structural damage and progression of degenerative findings in the contralateral knee and do not specify the medial or lateral knee compartment.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, these data were not available as in the clinical standard only a pelvic overview X-Ray was made to check for loosening of the prosthesis. We expect that the leg alignment has only a marginal effect on the results as previous work showed that the implantation of a hip prosthesis only led to a slight increased varus alignment (1 • ) of the operated leg (van Drongelen et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, restoring FO has a positive effect on isometric hip abductor strength [ 16 , 17 ], walking speed, and knee flexion and extension during walking 1 year after THA [ 18 ]. Restored FO has also been shown to influence knee joint moments but has no apparent impact on hip joint moments [ 19 ]. Most studies have focused on the FO in relation to gait and function.…”
Section: Introductionmentioning
confidence: 99%
“…The peak external knee and hip adduction moment during the first (KAM1 and HAM1) and second (KAM2 and HAM2) half of the stance were computed for each trial (normalized to body weight and expressed in newton meters per kilogram) and averaged over the trials. As has been published previously [26], kinematic parameters during the stance phase of gait were also extracted (a) for the hip: the maximum adduction angle in the frontal plane, the maximum flexion and extension angle, and the hip RoM in the sagittal plane; (b) for the knee: the maximum flexion and extension angle, as well as the RoM in the sagittal plane (the difference between the maximum flexion in the first half and the maximum extension during the second half of the stance); (c) for the trunk: maximum sideward displacement (LTD-lateral displacement of the trunk relative to the supporting limb); (d) for the foot: mean progression angle in the transverse plane (FPA-the angle of the long axis of the foot segment relative to the direction of walking). Furthermore, the pelvic drop of the contralateral leg during the swing phase was determined.…”
Section: Gait Analysismentioning
confidence: 67%
“…The 3D model was made using sterEOS ® (EOS imaging, SA, Paris, France) and was then used for planning the prosthesis (hipEOS ® , EOS imaging, SA, Paris, France). From the 3D reconstruction, five clinical leg parameters, which were described in detail elsewhere [25,26], were considered to assess the leg alignment ( Figure 1).…”
Section: Radiographic Measurementsmentioning
confidence: 99%